2013
DOI: 10.1007/s13337-013-0131-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profile of Penaeus monodon Ubiquitin Conjugating Enzyme (PmUbc) at Protein Level in White spot syndrome virus Challenged Shrimp

Abstract: White spot syndrome virus (WSSV) is one of the major pathogens in shrimp aquaculture. Four proteins of WSSV are predicted to encode a RING H2 domain, which in presence of ubiquitin conjugating enzyme (E2) in shrimps can function as viral E3 ligase and modulate the host ubiquitin proteasome pathway. Modulation of host ubiquitin proteasome pathway by viral proteins is implicated in viral pathogenesis. In the present study, expression profile of Penaeus monodon Ubiquitin conjugating enzyme (PmUbc) was studied at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Their study also revealed a weak expression of PvUbc in uninfected shrimp, suggesting that PvUbc expression is induced in WSSV infection till 48 h.a.i. Keezhedath et al (2013), the ubiquitin increased expression in P. monodon (PmUbc) post WSSV infection. In our study, the groups 24 and 72 h.a.i., ubiquitin protein had greater expression, agreeing with the findings of the authors cited above.…”
Section: Discussionmentioning
confidence: 93%
“…Their study also revealed a weak expression of PvUbc in uninfected shrimp, suggesting that PvUbc expression is induced in WSSV infection till 48 h.a.i. Keezhedath et al (2013), the ubiquitin increased expression in P. monodon (PmUbc) post WSSV infection. In our study, the groups 24 and 72 h.a.i., ubiquitin protein had greater expression, agreeing with the findings of the authors cited above.…”
Section: Discussionmentioning
confidence: 93%
“…This pathway also participated in viral infection and assists activities required of different aspect of virus life cycle, such as entry, replication and shedding [ 94 ]. Recently, various reports have been conducted showing the hijack of UPP pathway to regulate cellular intrinsic antiviral activities and innate immunity induced by WSSV [ 95 , 96 ]. E3 ubiquitin-protein ligase HUWE1 with the highest up changes after WSSV chanllenge was found in M .…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis presented in this paper provides a snapshot of ubiquitination as a host-pathogen immune response strategy in shrimp. Most current studies have shown that microbial infection of shrimp could induce ubiquitination through ubiquitin-conjugating enzymes, ubiquitin ligases, or ubiquitinated substrates ( 64 , 85 , 104 ). On the one hand, the ubiquitin system in shrimp could be exploited as a mechanism to resist pathogen invasion or annexed by microbial pathogens for replication and survival.…”
Section: Summary and Future Perspectivementioning
confidence: 99%
“…Some viral proteins act as E3 ubiquitin ligases to promote viral infection and survival using the host ubiquitin system. The RING proteins of WSSV, including WSSV199, WSSV222, WSSV249, and WSSV403, could serve as E3 ligases to coopt the ubiquitin-proteasome pathway of shrimp for viral replication ( 74 , 76 , 104 ). Furthermore, WSSV249 acts as an E3 ligase through interaction of ubiquitin-conjugating enzyme E2 for viral pathogenesis in P. vannamei ( 105 ).…”
Section: Summary and Future Perspectivementioning
confidence: 99%